2022
DOI: 10.24043/isj.388
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking destination success: An island perspective

Abstract: The global tourism industry has shifted due to COVID-19, with tourism-dependent islands facing a dire need to realign and reconstruct their tourism offerings to remain competitive. The traditional mass tourism model that has dominated island development has to be re-examined in this new tourism environment with new mindsets regarding the current conditions for destination success. This paper aims to promote an understanding of destination success in an island context and to identify which determinants are crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There may be implications for DMOs in other locations even though this paper emphasizes the significance of DMOs in the Atlantic region. According to one study's results, island destinations are at a turning point in their development, and major strategic changes are required to support the DMOs' definition of success for these destinations going forward [76]. While many of the studies discussed DMO roles, the studies looking into climate change impacts are still sparse when it comes to tourism and DMO practices.…”
Section: Discussionmentioning
confidence: 99%
“…There may be implications for DMOs in other locations even though this paper emphasizes the significance of DMOs in the Atlantic region. According to one study's results, island destinations are at a turning point in their development, and major strategic changes are required to support the DMOs' definition of success for these destinations going forward [76]. While many of the studies discussed DMO roles, the studies looking into climate change impacts are still sparse when it comes to tourism and DMO practices.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have suggested that island economies on a sustainable path to recovery should pivot on the local people as the core [26][27][28]. Among the many influencing factors associated with island resilience, the contribution of migration to island resilience has been confirmed [29,30].…”
Section: Related Workmentioning
confidence: 99%
“…However, the developmental benefits of tourism have been severely constrained over the years owing to the many socio-economic and environmental challenges that have plagued the islands as a result of rapid, unplanned growth. Foreign ownership, high leakage, expatriate domination of management at high levels, overexploitation of limited physical resources are some of the ills of mass tourism development (Lewis-Cameron and Brown, 2022).…”
mentioning
confidence: 99%